Predictive roles of interpeduncular and pontomesencephalic angle measurements, which are anatomical landmarks in cranial MRI, in the differential diagnosis of pediatric headache (Annals of Medical Research, 2022)
Aim: This study aims to comparatively assess the interpeduncular and pontomesencephalic angles in the cranial magnetic resonance imaging (MRI) images of pediatric headache patients. Thus, we think that it will contribute to the studies to be conducted for the objective evaluation of pediatric headache requiring the use of cerebral MRI.Materials and Methods: This retrospective study was performed using clinical and radiological data extracted from the medical files of 157 patients and 49 controls. Our population consisted of 101 females (49 %) and 105 males (51 %).  The patient population was divided into 4 categories as follows: non-specific headache (thought to be of the tension-type), vasovagal syncope, sinusitis, and epilepsy. Interpeduncular (IP) and pontomesencephalic (PM) angles of patients and control groups were compared on MR images.Results: The population average age in this series was 11.05 ± 3.78 (range, 5 to 17) years. The comparison of IP angleyielded statistically significant differences between tension-typeheadache-epilepsy, tension type-headache- vasovagal syncope, epilepsy-control, and vasovagal syncope-control groups. Multiple comparisons for PM angle demonstrated remarkable differences between headache-control, epilepsy-control, epilepsy-sinusitis, and control- vasovagal syncope groups.Conclusion: Our results indicated that measurements of IP and PM angles on the cerebral MRI views of children whose etiology could not be clarified and for whom cranial imaging was required, may yield valuable data in the differential diagnosis. We are of the opinion that by working on larger data sets in the future, more valuable data can be obtained in differential diagnosis.
Keywords: Headache; children; cranial; magnetic resonance imaging; interpeduncular angle; pontomesencephalic angle